Persepsi Masyarakat Muslim Terhadap Praktik Suntik Putih: Studi Kasus Pada Salon Kecantikan - Nadila Okta Mega Sari; Siti Nurhayati (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2022)
Whitening injection was a treatment method used by injecting vitamin C directly into the blood vessels. It is forbidden in Islamic law. It was necessary to know more about the background of the social reality of the community, social factors of the community, social symptoms and the condition of the community in Pule Village, Kandat District, Kediri Regency, where was the reason why people continue to practice whitening injections. according to the perspective of the sociology of Islamic law, it was seen as a change in social behaviour from strict adherence to sharia law. People had no obedience and practice of Islamic law in their social behaviour in society. It was supposed to be illegal, but it was still done by salon owners and customers. Salon owners still provide whitening injection treatments because of economic factors. Meanwhile, customers still did whitening injections because of aesthetic factors. Meanwhile, some people in Pule Village, Kandat District, Kediri Regency, know the law regarding the prohibition of white injection so they did not practice whitening injection. Therefore, religious leaders as social controllers who understand Islamic sharia should educate the public about how the white injection law was to prevent this practice.